Webinar insights: Impact of outsourcing agricultural services on smallholder farmers - Nguyen, Vi (CGIAR, 2024)
One of the emerging developments in agrifood systems worldwide is the rise of enterprises which provide farmers with “outsource” agricultural services. These services are emerging in various agricultural operations traditionally carried out by farmers themselves. But what has driven this growth? And how might they impact the future of farms?